Implementation of an Affective Model for MASOES (Latin-American Journal of Computing, 2017)
Different authors seek to improve the interactionbetween intelligent agents in multi-agent systems, an example isthe affective model of MASOES, which through the generationof emotions promotes different types of behaviors. Although thisaffective model has been formally verified at the design level,it has not been verified at the implementation level. This workpresents methodologically the implementation for the affectivemodel of MASOES on a multiagent system, verifying the requiredat the design level by this multiagent architecture, in order toprovide an environment for the interaction between the emotionalprocesses and the different functions of an agent. In addition, wepropose the calculation of Social Emotion, allowing to describethe collective emotional state of a group of emotional agents.